Optimization of Process Parameter on AA8052 Friction Stir Welding Using Taguchi’s Method - Pankaj Sharma; S. Baskar; Puneet Joshi; T. A. Raja; Santosh Kumar Sahu; Medapati Sreenivasa Reddy; M. Rudra Naik (Advances in Materials Science and Engineering)
The Taguchi method of experimental design was employed in this study to scrutinize the impact of welding processing factors, including rotating speed, travelling speed, and pin profile on ultimate tensile strength, microhardness, and impact strength of the Friction Stir Welded AA 8052 joint. The S/N values for each process specification were calculated using an orthogonal array of L9 design. The 1150 rpm and 28.5 mm/min were the greatest tensile strength, microhardness, S/N evaluation parameters, respectively, and a used cylinder pin. A combination of 1150 rpm and 32.5 mm/s and a conical cylindrical pin provided the best impact toughness results. According to the analysis of variance, the spinning speed, travel feed, and pin shape had a 37.34% impact on ultimate strength and a further 34.33% impact on microhardness. A second set of tests verified the findings, with tensile strength of 349.96 MPa, hardness of 115.31 H, and impact strength of 7.95 kJ.